Effect of diameter class, ethephon concentration and environment variables on gum production from Acacia tortilis in arid zone of western Rajasthan - Verma, Archana; Pareek, Kamlesh; Shiran , K (Annals of Arid Zone, 2023)
Acacia tortilis is one of the important tree species for gum production in aridregions of western Rajasthan. However, the studies are lacking in standardization ofgum production in this species. Therefore, study was carried out to standardize theethephon dose in various diameter classes and the effect of climatic factors on gumproduction in different seasons. Results showed that the high statistical difference forgum yield in different season and different diameter classes with varying concentrationof ethephon. The production of gum was more in summer season (S1) i.e., 298.2 g tree-1,diameter class (D3) (293 g tree-1) and ethephon treatment (T2) (314.7 g tree-1). Correlationand regression analysis showed high association of gum yield with temperature andrelative humidity. The regression analysis revealed 99% and 86% variability in gumyield due to mean temperature and mean relative humidity, respectively. The resultswill help in using the standardized dose of ethephon in various diameter classes alongwith understanding the effect of various climatic factors on gum production in A. tortilis